MOLECULAR DETECTION OF BLACTX-M AND BLASHV GENES IN ESCHERICHIA COLI AND KLEBSIELLA PNEUMONIAE IN A TERTIARY CARE HOSPITAL IN PUDUCHERRY,INDIA - G.MUTHU; G.TAMIL INIYAN; J.SHANMUGAM; T.MANGAIYARKARASI (International Journal of Pharma and Bio Sciences, 2014)
Extended-spectrum β-lactamases producing Enterobacteria represent a rapidly emerging resistance problem in many countries. The present study was undertaken to find out the presence of blaCTX-M3 and blaSHV genes by PCR technique among clinical isolates of Escherichia coli and Klebsiella pneumoniae. A total of 186 faecal specimens were collected in our hospital, were subjected to isolation, identification of E.coli and K. pneumoniae, antimicrobial susceptibility testing was performed by disc diffusion method as per Clinical Laboratory Standard Institute.The PCR detection of E.coli revealed 40/50 (80%) for CTX-M-3 and (24/50) 48% for blaSHV genes were positive. Moreover, antimicrobial resistance for E. coli showed 74% to cefotaxime, 62% to ceftriaxone, K. pneumoniae showed 72% of CTX-M-3 and 80% of blaSHV positive genes and resistance to cefotaxime (84%), ceftriaxone (56%), ceftazidime (66%), cefuraxime (68%), cefoperazone (58%), blaCTX-M3 and blaSHV genes transfers are possible mechanisms for wide prevalence of cephalosporin resistant among E.coli and K. pneumoniae strains.